Obstetricians’ views on extending the 12-week abortion limit in Belgium: A qualitative study - Fien De Meyer; Kim Beernaert; Sarah Van de Velde; Sigrid Sterckx; Kristof Van Assche (PLoS ONE, 2025)
Aim This study explores the views of obstetricians on a potential extension of the 12-week limit on elective abortion in Belgium. It aims to investigate perspectives from a distinct group of providers who already have experience with later abortion, albeit provided on medical grounds. These insights could help identify and navigate perceived challenges and opportunities of extending the abortion time limit. Methods We conducted semi-structured qualitative interviews with 23 hospital obstetricians who are involved in abortion on medical grounds in Flanders, Belgium. We coded and thematically analyzed interview transcripts with NVivo software. Results We discerned three major themes in obstetricians’ views: 1) Concerns about later abortion techniques; 2) Psychosocial hardships justifying later abortion; and 3) Fetal viability and feticide considerations. Minor themes are: 4) Limited impact on abortion for fetal anomaly; 5) Abortion travel and associated harms; and 6) Sex-selective abortion. Conclusion Flemish hospital obstetricians highlight both moral and technical challenges associated with extending the abortion time limit, primarily relating to surgical abortion methods and the organization of care. This study finds that, if an extended limit were to be adopted, additional policies and safeguards would facilitate implementation and foster interest among obstetricians in providing services. These include education and technical training of providers in later abortion care, centralization of provision, appropriate facilities, prepared teams, value workshops, and adequate state financing.